Analisis Framing Budaya Ngopi Dalam Film Filosofi Kopi 2: Ben & Jody - Cahyani, Ni Putu Ayu; Pradipta, Ade Devia; Joni, I Dewa Ayu Sugiarica; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium, 2024)
Film as one of the mass communication media is able to be a instrument of representation in society culture. Often, the story in some films raises cultural issues that have begun to shift towards a more modern direction in society. This research focuses on how the coffee culture in the film Coffee Philosophy 2: Ben & Jody is able to represent a new coffee culture to consumers and coffee businesses. This study used Zhongdang Pan & M. Kosikchi's framing analysis to frame scenes in the film Coffee Philosophy 2: Ben & Jody and used a type of descriptive qualitative research with a constructivism paradigm. The theory used in this study is Erving Goffman's Framing theory which can be used to frame stories through experience to form a reality. The coffee culture formed in the film Coffee Philosophy 2: Ben & Jody is that drinking coffee is no longer just enjoying the taste of a cup of coffee but coffee is now part of the lifestyle and social class in society.